Microbiology : - Stokes, Gerald V. (J&S Pub. Co., 1993)
This is a 194 page, 507 question review book designed for rapid review for USMLE, Step 1 and other licensure examinations. Questions are grouped in sets of 3-5 followed by answers and a tutorial on the topic covered by the question set. Topics covered include: Bacteriology, Virology, Immunology, Parasitology, and Mycology. Ideal for 2 day review for USMLE, Step 1. Black and white illustrations.